Pengaruh Pupuk Kandang Kambing dan Mikoriza terhadap Pertumbuhan dan Produksi Tanaman Melon - Damanik, Endi Indra Paska; Panggabean, Ellen L. (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This study aimed to determine the effect of goat manure and mycorrhiza on the growth and yield of melon plants (Cucumis melo L.). The research was conducted at the Experimental Field of the Faculty of Agriculture, Universitas Medan Area, from February to May 2025, using a completely randomized design (CRD) with a factorial arrangement of two factors: goat manure dosage (0, 10, and 20 tons/ha) and mycorrhiza concentration (0, 5, and 10 g/plant), with three replications. The observed parameters included plant height, leaf area, number of fruits, fruit weight per plant, and sweetness level. The results showed that the combination of goat manure and mycorrhiza significantly affected the growth and yield of melon plants. The treatment combination of 20 tons/ha goat manure and 10 g/plant mycorrhiza produced the highest plant height, fruit weight, and sugar content. The integration of these two organic inputs improved nutrient uptake efficiency, enhanced soil structure, and increased fruit quality. This approach has the potential to serve as an environmentally friendly cultivation strategy for sustainably increasing melon productivity.